Hydroxycinnamoyltransferases in plant metabolism - Petersen, Maike (Phytochemistry reviews, 2016)
Hydroxycinnamoyltransferases are enzymes transferring hydroxycinnamoyl units like cinnamoyl, 4-coumaroyl, caffeoyl, feruloyl and sinapoyl moieties from an activating residue such as coenzyme A or glucose or activated as hydroxycinnamoyl ester (e.g. chlorogenate) to an acceptor molecule, most commonly to an OH or NH 2 group as ester or amide. The hydroxycinnamoyl groups play either a “decorating” role or are building blocks of more complex structures. Proteins catalysing hydroxycinnamoyl transfer have been known for many decades and are nowadays investigated on molecular and structural levels. At least four different protein families give rise to enzymes with hydroxycinnamoyltransferase activity: serine carboxypeptidase-like proteins, tyramine hydroxycinnamoyltransferase-like enzymes, BAHD acyltransferases and GDSL-lipase/esterase-like enzymes. Interestingly, the same or very similar products can be formed by enzymes from different enzyme classes and using differently activated hydroxycinnamoyl units. This review will summarise the current literature data on the features of hydroxycinnamoyltransferases from the four different enzyme groups.